Activation of peroxymonosulfate system by copper-based catalyst for degradation of naproxen: Mechanisms and pathways. (August 2019) - Chi, Huizhong; Wang, Zeyu; He, Xu; Zhang, Jianqiao; Wang, Da; Ma, Jun
Abstract: Organic degradation by zero-valent metal (ZVM)-activated peroxymonosulfate (PMS) systems has drawn great attention in water treatment. Among various types of ZVM, zero-valent copper (ZVC) showed greatest activating capacity. However, the disadvantages of the released Cu 2+ limit the practical utilization of ZVC. In this study, the activation capacity of four normal-sized copper catalysts, namely, copper sheet, graphene-copper sheet, copper foam, and graphene-copper foam, for PMS was investigated using Naproxen (NPX) as the probe compound. Results showed that the degradation efficiency of NPX increased by 10%, while the release of Cu 2+ decreased by 30% by coating the copper with graphene. Stability tests showed that all of the four catalysts exhibited considerable stability in PMS activation. Furthermore, we found for the first time that the hydroxyl radical was the dominant species in the degradation of NPX rather than the sulfate radical, which was proved by ESR and radical scavenging experiments. Finally, six intermediates were identified by HPLC-MS/MS, and the degradation pathways were proposed. This study confirmed the feasibility of graphene coating on metals to achieve the enhancement of PMS activation. Highlights: The activation capacity of four types of normal-sized zero-valent copper catalyst on PMS was investigated. The release of copper ions could be inhibited by graphene coating, while the degradation efficiencies of NPX increased. PMS acted as an electron acceptor in the four copper-catalyzed PMS systems. Hydroxyl radical was the dominant species in the degradation of NPX, and water acted as the radical precursor.